Analisis Penerimaan Aplikasi e-PKH Pasca Pandemi Covid-19 pada Dinas Sosial Kabupaten Tangerang Menggunakan Metode TAM - Monalisa, Monalisa (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
This evaluation research was carried out with the aim of assessing how effective the use of the e-PKH application is in the Tangerang Regency Social Service, especially by PKH social assistants after the Covid-19 pandemic which spread across the region, namely 29 sub-districts. This research involved 69 PKH social assistants as subjects. Data collection used document methods, questionnaires and direct interviews. The t test that was carried out resulted in the Perception of Usefulness variable having a calculated t value of 0.054 and a t table of 0.678, which shows a picture of the e-PKH Application Effectiveness Variable (Y) negatively influencing the e-PKH application usefulness variable (X1). Meanwhile, the e-PKH application ease variable shows a calculated t value that is higher than the t table (3.967 > 0.678), meaning that the e-PKH application effectiveness variable (Y) positively influences the e-PKH application ease variable (X2). The results of the analysis also show that the calculated F value exceeds the F table (10.055 > 2.74), so the conclusion obtained is that all independent variables, namely the usefulness of the e-PKH application and the ease of the e-PKH application, simultaneously influence the dependent variable, namely the effectiveness of the e-PKH application.